WERNER SYNDROME: CLINICAL EVALUATION OF TWO CASES AND A NOVEL MUTATION - (:unkn) unknown (MEDECINE ET HYGIENE, 2014)
Werner syndrome: clinical evaluation of two cases and a novel mutation: Werner syndrome (WS) is a premature aging disorder, inherited in an autosomal recessive pattern and caused by the mutation in the WRN gene. In this report we describe two male patients with negative family history who demonstrate characteristic findings of WS, with different mutations, including one novel mutation. The first case was a 47-year-old man who had been suffering from large, ischemic ulcers on both legs for 7 years. Physical examination revealed a thin and short man with severe wasting of all extremities. He had a high-pitched voice, hoarseness, a characteristic bird-like facies, bilateral cataracts, generalized osteoporosis, hypotrichosis, atrophic and poikilodermic skin, flexion contractures of hands, feet and knees, and soft tissue calcifications. Laboratory investigations revealed anemia, high erythrocyte sedimentation rate, low creatinine clearance, and high liver enzymes. Genetic analysis showed a homozygous novel lbp-deletion in exon 19 of WRN, 2426/27delG, causing frameshift and protein truncation R809SfsX2, which has not been described before. The second case was a 23-year-old man who was referred for large callosities on both feet, present for 7 years. He complained of weakness, weight loss, wasting of muscles, and early graying of hair. The entire skin was thin, wrinkled and dry. Generalized hypotrichosis, scattered ephelid-like macules, sclerotic fingers, calcinosis cutis on ears, hyperpigmentation on elbows were the other alterations of skin. Skeletal survey revealed osteoporosis. Genetic analysis showed a homozygous known pathogenic splice site mutation c.3460-2A>G, causing skipping of Exon 30 in WRN.
Keywords: Premature aging; Werner syndrome; WRN protein; DNA helicase